Adsorbent
By using amorphous magnesium silicate compounds with low alkali metal content and high solid acidity as adsorbents, the problems of large amounts of existing adsorbents and large amounts of waste are solved, and the effects of efficient adsorption and resource conservation are achieved, supporting the realization of the Sustainable Development Goals.
Patent Information
- Application Number
- CN202380061207.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-30
- Filing Date
- 2023-07-13
- Publication Date
- 2025-04-01
AI Technical Summary
When adsorbing alkaline catalysts containing alkali metals, existing adsorbents require a large amount of adsorbent, resulting in a decrease in yield and a large amount of waste. It is necessary to improve the adsorption capacity of the adsorbent to reduce the amount of use.
Amorphous magnesium silicate compounds with low alkali metal content and high solid acidity are used as adsorbents, and their adsorption capacity is improved by adjusting the pH value during the synthesis process, heating and maturation treatment and acid treatment.
It significantly improves the adsorption capacity of metal ions such as K+, Na+, Ni+, etc., reduces the use of adsorbents, reduces the cost of energy consumption and waste disposal, and supports the realization of the sustainable development goals.
Smart Images

Figure CN119744196A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a novel adsorbent for adsorbing adsorbates such as alkali metals. Background Art
[0002] In chemical products, impurities such as catalysts used in synthesis, unreacted raw materials, and by-products during reaction sometimes remain in trace amounts. From the perspective of improving product quality, it is required to effectively remove these impurities. As methods for removing such impurities, for example, there can be cited methods of removing impurities by methods such as neutralization, distillation, extraction, or adsorption in the manufacturing process of chemical products. Among them, adsorption methods, especially methods using adsorbents, can be used as simple methods.
[0003] For example, polyurethane foam is produced by polymerizing a polyol component and an isocyanate component as raw materials. The polyol used to produce polyurethane foam includes polyether polyol, polymer polyol, polyester polyol, etc., which are used in any combination according to the properties of the target polyurethane. For example, polyether polyol is produced by addition polymerization of propylene oxide and glycerol in the presence of an alkaline catalyst containing an alkali metal, but the residual catalyst after purification is required to reach a purity infinitely close to zero.
[0004] In order to achieve such a high level of purity, an adsorbent capable of removing alkaline catalysts containing alkali metals by adsorption is used in the production of polyether polyols. The adsorbent used here is generally a synthetic product such as molecular sieve, activated alumina, synthetic magnesium silicate, synthetic aluminum silicate, activated carbon, etc.; a natural product; a processed product of natural products such as acid clay, activated clay, etc., without particular limitation. For example, in Patent Document 1, as an adsorbent capable of removing alkaline catalysts containing alkali metals by adsorption, an adsorbent composed of an amorphous synthetic hydrous magnesium silicate compound having a chemical formula, a BET specific surface area, an alkali metal content, and an average particle size within specific ranges is disclosed. Prior art literature Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2004-75674 Summary of the invention Problems to be solved by the invention
[0006] However, in these conventional adsorbents, a large amount of adsorbent is required for the alkaline metal-containing basic catalyst as the adsorbate, so the yield of polyether polyol is reduced due to adsorption by the adsorbent, and a large amount of waste is generated after purification. In order to solve such problems, it is strongly required to improve the adsorption capacity of the adsorbent to reduce the amount of adsorbent used.
[0007] Therefore, an object of the present invention is to provide a novel adsorbent having a high adsorption capacity and capable of adsorbing an adsorbate with a relatively small usage amount. Means of solving problems
[0008] In order to achieve the above object, the present inventors conducted intensive research and found that by using an amorphous magnesium silicate compound with a low alkali metal content and high solid acidity as an adsorbent, K + 、Na + 、Ni + The adsorption capacity of metal ions is improved. The present invention is completed based on the above findings and includes the following embodiments.
[0009] (First Publication) The first disclosure of the present invention is an adsorbent comprising an amorphous magnesium silicate compound, wherein the alkali metal content of the magnesium silicate compound is 1.20 mass % or less and the solid acid amount of the magnesium silicate compound is 0.70 mmol / g or more.
[0010] (Second Publication) The second disclosure of the present invention is the one according to the first disclosure, wherein the magnesium silicate compound is a compound represented by the following formula (1). (MgO) x ·SiO2·mH2O···(1) [In formula (1), x is a number satisfying 0.1≤x≤0.5, and m is a number satisfying 0.1≤m≤1.5.]
[0011] (3rd Publication) The third disclosure of the present invention is that in the first disclosure or the second disclosure, the magnesium silicate compound has a BET specific surface area of 200 m 2 / g~1000m 2 / g.
[0012] (4th Publication) The fourth disclosure of the present invention is that in any one of the first disclosure to the third disclosure, the total pore volume (total pore volume) of the magnesium silicate compound is 0.40 cm 3 / g~1.50cm 3 / g.
[0013] (5th Publication) The fifth disclosure of the present invention is a method for reducing the alkali metal content in a polyether polyol, comprising contacting a polyether polyol containing an alkali metal-containing basic catalyst with the adsorbent described in any one of the first to fourth disclosures. Effects of the Invention
[0014] According to the present invention, it is possible to provide a new adsorbent having a high adsorption capacity and capable of adsorbing an adsorbate with a small usage amount. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is the powder X-ray diffraction pattern of the magnesium silicate compound of Example 2. Figure 2 This is the powder X-ray diffraction pattern of the magnesium silicate compound of Example 4. DETAILED DESCRIPTION
[0016] Hereinafter, preferred embodiments of the adsorbent of the present invention will be described in detail. In the present specification, various numerical ranges are ranges including the upper and lower limits unless otherwise specified.
[0017] [Adsorbent] The adsorbent according to one embodiment of the present invention comprises or is composed of an amorphous magnesium silicate compound. The alkali metal content of the magnesium silicate compound is 1.20 mass % or less. In addition, the solid acid content of the magnesium silicate compound is 0.70 mmol / g or more.
[0018] The adsorbent of the present embodiment contains or is composed of the amorphous magnesium silicate compound having a low alkali metal content and high solid acidity as described above, and can + 、Na + 、Ni + It has excellent adsorption capacity for metal ions such as magnesium silicate. Moreover, since its adsorption capacity is much higher than that of the adsorbent composed of the previous magnesium silicate compound, the adsorbent of this embodiment can significantly reduce its usage compared with such previous adsorbents. That is, the adsorbent of this embodiment is a new adsorbent that has a very high adsorption capacity and can adsorb the adsorbate with a smaller usage amount compared with the adsorbent composed of the previous magnesium silicate compound. In addition, the adsorbent of this embodiment also has the following advantages: it can help reduce energy consumption and waste disposal, etc., and can contribute to the realization of the SDGs (Sustainable Development Goals) adopted at the United Nations Summit.
[0019] (Magnesium silicate compound) As described above, the adsorbent according to one embodiment of the present invention includes or consists of an amorphous magnesium silicate compound. Here, the term "amorphous magnesium silicate compound" refers to a magnesium silicate compound that is amorphous in its powder X-ray diffraction pattern.
[0020] (Alkali metal content) Furthermore, in the present embodiment, the alkali metal content of the magnesium silicate compound is 1.20 mass % or less.
[0021] Such an alkali metal content below a specific amount can be obtained, for example, by adjusting the pH of the reaction slurry to be lowered when synthesizing the magnesium silicate compound described later, or by performing a heating aging treatment and / or an acid treatment after the synthesis. For example, by reducing the pH of the reaction slurry when synthesizing the magnesium silicate compound, the alkali metal content can be reduced. It is also believed that if a heating aging treatment is performed after the synthesis of the magnesium silicate compound, the alkali metal content can be reduced by promoting the dissolution and precipitation of the magnesium silicate compound. In addition, if an acid treatment is performed after the synthesis of the magnesium silicate compound, the alkali metal component contained is replaced by the proton of the acid, so the alkali metal content can be reduced.
[0022] In addition, in this specification, an alkali metal component refers to an alkali metal such as sodium and potassium derived from a raw material, for example.
[0023] The alkali metal content of the magnesium silicate compound is preferably 1.10% by mass or less, and more preferably 1.00% by mass or less. The lower limit of the alkali metal content of the magnesium silicate compound is not particularly limited, and an example thereof is 0.001% by mass.
[0024] (Solid acid amount) In one embodiment of the present invention, the solid acid amount of the magnesium silicate compound is 0.70 mmol / g or more.
[0025] Such a specific amount or more of solid acid can be obtained by the same method as the above-mentioned alkali metal content. That is, such a specific amount or more of solid acid can be obtained, for example, by adjusting the pH of the reaction slurry to be reduced during the synthesis of magnesium silicate compounds described later, or by performing heating aging treatment and / or acid treatment after synthesis. For example, by reducing the pH of the reaction slurry during the synthesis of magnesium silicate compounds, the alkali metal content can be reduced, and the solid acid amount can be increased. It is also believed that if a heating aging treatment is performed after the synthesis of magnesium silicate compounds, the alkali metal content can be reduced by promoting the dissolution of magnesium silicate compounds, and the solid acid amount can be increased. In addition, if an acid treatment is performed after the synthesis of magnesium silicate compounds, the alkali metal components contained are replaced by protons of the acid, so the alkali metal content can be reduced, and the solid acid amount can be increased.
[0026] The solid acid amount of the magnesium silicate compound is preferably 1.00 mmol / g or more, and more preferably 1.50 mmol / g or more. The upper limit of the solid acid amount of the magnesium silicate compound is not particularly limited, and is, for example, 10.00 mmol / g.
[0027] In addition, the specific method of measuring the amount of solid acid will be described in the examples given later.
[0028] Thus, the magnesium silicate compound according to one embodiment of the present invention can exhibit very excellent adsorption capacity for various metal ions by having an alkali metal content of less than the above-mentioned specific amount and having a high solid acid content of more than the above-mentioned specific amount. Therefore, the adsorbent according to this embodiment can adsorb various metal ions with a smaller usage amount than the adsorbent composed of the conventional magnesium silicate compound.
[0029] (Chemical formula) In the present embodiment, the magnesium silicate compound is amorphous and is not particularly limited except that it has an alkali metal content of not more than the above-specified amount and a high solid acid content of not less than the above-specified amount. It is preferably a hydrous magnesium silicate compound represented by the following formula (1). (MgO) x ·SiO2·mH2O···(1) [In formula (1), x is a number satisfying 0.1≤x≤0.5. m is a number satisfying 0.1≤m≤1.5.]
[0030] When the magnesium silicate compound is a hydrous magnesium silicate compound represented by the formula (1), the excellent adsorption capacity for the above-mentioned metal ions can be more reliably exerted.
[0031] In the above formula (1), the preferred range of x is 0.2≤x≤0.35.
[0032] (BET specific surface area) In this embodiment, the BET specific surface area of the magnesium silicate compound is preferably 200 m 2 / g~1000m 2 When the BET specific surface area of the magnesium silicate compound is within such a range, a certain amount of adsorption or more can be ensured, and thus the excellent adsorption capacity for the above-mentioned metal ions can be more reliably exhibited.
[0033] The BET specific surface area of the magnesium silicate compound is more preferably 220 m 2 / g or more, more preferably 250m 2 / g or more. In addition, the BET specific surface area of the magnesium silicate compound is more preferably 900m 2 / g or less, more preferably 800m 2 / g or less.
[0034] In addition, in this specification, BET specific surface area means the specific surface area of a magnesium silicate compound measured by the BET method. The specific measurement method of the BET specific surface area is described in the Examples described later.
[0035] (Total pore volume) In this embodiment, the total pore volume of the magnesium silicate compound is preferably 0.40 cm3 / g~1.50cm 3 When the total pore volume of the magnesium silicate compound is within such a range, a certain amount of adsorption can be ensured, and thus the excellent adsorption capacity for the above-mentioned metal ions can be more reliably exhibited.
[0036] The total pore volume of the magnesium silicate compound is more preferably 0.50 cm 3 / g or more. In addition, the total pore volume of the magnesium silicate compound is more preferably 1.20 cm 3 / g or less.
[0037] In addition, the specific measurement method of the total pore volume will be described in the examples mentioned later.
[0038] (Average particle size) In this embodiment, the average particle size of the magnesium silicate compound is 2.0 μm to 60.0 μm. If the average particle size of the magnesium silicate compound is within this range, the specific surface area can be increased, and a certain amount of adsorption can be ensured, so that the excellent adsorption capacity for the above metal ions can be more reliably exerted.
[0039] The average particle size of the magnesium silicate compound is more preferably 5.0 μm or more. In addition, the average particle size of the magnesium silicate compound is more preferably 50.0 μm or less.
[0040] In addition, the specific measurement method of the average particle size will be described in the examples given later.
[0041] [Manufacturing method] Hereinafter, a method for producing a magnesium silicate compound constituting an adsorbent according to an embodiment of the present invention will be described by taking the above-mentioned method for producing a hydrated magnesium silicate compound as an example. It should be noted that the magnesium silicate compound that can be used as the adsorbent of the present invention is amorphous, and as long as it can be produced into an amorphous magnesium silicate compound having an alkali metal content of not more than the above-mentioned specific amount and a high solid acid content of not less than the above-mentioned specific amount, the production method and conditions are not limited in any way.
[0042] (Synthesis process) The above-mentioned hydrated magnesium silicate compound can be synthesized by reacting a water-soluble magnesium compound with a water-soluble silicate compound. Examples of the water-soluble magnesium compound include magnesium chloride, magnesium sulfate, magnesium nitrate, and the like. Examples of the water-soluble silicate compound include sodium silicate represented by the general formula Na2O·nSiO2 (n=2 to 4), which is commonly referred to as water glass; sodium metasilicate; sodium orthosilicate; alkali metal silicate salts such as potassium silicate, and the like. Among them, the water-soluble silicate compound preferably uses No. 3 water glass.
[0043] The reaction may be a batch reaction in which a certain amount of magnesium compound aqueous solution and a certain amount of silicate compound aqueous solution are simultaneously poured into a reaction tank, or a continuous reaction in which a certain amount of magnesium compound aqueous solution and a certain amount of silicate compound aqueous solution are continuously poured into a reaction tank to continuously obtain a reaction slurry. From the viewpoint of production efficiency, a continuous reaction is advantageous.
[0044] The reaction temperature is not particularly limited, and for example, a temperature of 15° C. to 60° C. may be used. For example, the reaction tank may be placed in a thermostatic bath controlled at a certain temperature to allow the reaction to proceed, or a container containing an aqueous solution of a magnesium compound and a container containing an aqueous solution of a silicic acid compound may be placed in a thermostatic bath controlled at a certain temperature, and the solution is poured from each container into the reaction tank using a metering pump.
[0045] The reaction pH is, for example, 7 to 10, preferably 8.5 to 9.5. By adjusting the reaction pH within such a range, the primary particles of the synthesized hydrous magnesium silicate compound can be made into fine particles. By making the primary particles into fine particles, the specific surface area of the hydrous magnesium silicate compound increases, the adsorption site increases, and the adsorption capacity can be improved.
[0046] (Heating and aging process) The reaction slurry obtained by the above-mentioned synthesis step can be aged by heating and stirring. The aging temperature is, for example, 60°C to 120°C, preferably 70°C to 110°C, and more preferably 80°C to 100°C. The aging time is, for example, 0.5 hours to 18 hours, preferably 1 hour to 12 hours, and more preferably 2 hours to 6 hours. By heating and aging the synthesized hydrous magnesium silicate compound under such specific conditions, the specific surface area of the hydrous magnesium silicate compound increases, the adsorption site increases, and the adsorption capacity can be improved.
[0047] (Acid treatment process) The synthesized hydrous magnesium silicate compound can be acid-treated with an inorganic acid. By performing such an acid treatment, the alkali metal component in the synthesized hydrous magnesium silicate compound is replaced by the proton of the inorganic acid, and the solid acidity of the hydrous magnesium silicate compound is improved, thereby improving the adsorption capacity of alkali metal ions. It should be noted that the alkali metal component is, for example, sodium or potassium derived from the raw material.
[0048] The inorganic acid that can be used in the acid treatment step is not particularly limited, and examples thereof include sulfuric acid, hydrochloric acid, and nitric acid.
[0049] As a specific method of the acid treatment step, i.e., a specific method of replacing the alkali metal components in the synthesized hydrous magnesium silicate compound with protons of an inorganic acid, for example, a method of separating the reaction slurry into solid and liquid, washing the solid with a diluted inorganic acid, and then washing with water. As another method, a method of separating the reaction slurry into solid and liquid, suspending the solid in a diluted inorganic acid and stirring for a certain period of time, dehydrating, and then washing with water can be mentioned.
[0050] The concentration of the inorganic acid is, for example, 0.01 mol / L to 0.5 mol / L, preferably 0.02 mol / L to 0.2 mol / L. When the concentration of the diluted inorganic acid is 0.01 mol / L or more, the replacement of the proton and the alkali metal component in the inorganic acid is fully carried out. On the other hand, when the concentration of the diluted inorganic acid is 0.5 mol / L or less, the sulfate ion, chloride ion or nitrate ion of the inorganic acid is not easy to remain in the solid as impurities. In addition, when the concentration of the diluted inorganic acid is 0.5 mol / L or less, the magnesium in the magnesium silicate is not easily dissolved by the inorganic acid.
[0051] (Drying process) The method for drying the synthesized hydrous magnesium silicate compound is not particularly limited, and examples thereof include a shed drying method in which the dehydrated solid is placed in a stainless steel barrel and dried with hot air. Other drying methods include slurrying the dehydrated solid to a concentration of 100 g / L to 500 g / L in terms of solid content, and slurrying the solid using a ball mill, colloid mill, SC mill, -MILL or other wet pulverizer to adjust the shape of the dried product, and then use a spray drying method to dry it with a spray dryer. From the perspective of easily granulating the hydrous magnesium silicate compound into a spherical shape, the spray drying method is preferably used as the drying method. If the hydrous magnesium silicate compound is granulated into a spherical shape, it has the advantage of being easy to separate and remove after adsorption treatment.
[0052] The magnesium silicate compound obtained by the above production method is amorphous due to the reaction conditions during synthesis, the heating and aging step and / or the acid treatment step after synthesis, and has an alkali metal content of not more than the above specific amount and a high solid acid content of not less than the above specific amount.
[0053] Such a magnesium silicate compound can be used as an adsorbent for various industrial purposes, for example, and is particularly useful as an adsorbent for adsorbing and removing an alkali metal-containing basic catalyst during the production of a polyether polyol as described above.
[0054] [Method for reducing the alkali metal content in polyether polyol] Another embodiment of the present invention is a method for reducing the alkali metal content in a polyether polyol. The method comprises contacting a polyether polyol containing an alkali metal-containing basic catalyst with an adsorbent, wherein the adsorbent contains or consists of an amorphous magnesium silicate compound having an alkali metal content of not more than the above specific amount and having a high solid acid amount of not less than the above specific amount.
[0055] In the present reduction method, as described above, the adsorbent has a very excellent adsorption capacity capable of adsorbing various metal ions in a relatively small amount, so that the yield of the polyether polyol can be increased and the amount of waste generated after purification can be reduced.
[0056] Specific examples of methods for removing the residual alkali metal-containing basic catalyst contained in the polyether polyol by adsorption include a method in which the above-mentioned magnesium silicate compound is added as an adsorbent to the polyether polyol, the mixture is mixed, and then the adsorbent is separated and removed.
[0057] The amount of the adsorbent added depends on the amount of the residual alkali metal-containing basic catalyst. For example, the amount of the adsorbent added is 0.1 to 10.0% by mass, preferably 0.5 to 5.0% by mass, relative to the mass of the polyether polyol.
[0058] As the conditions for the adsorption treatment, for example, the adsorption treatment can be carried out under stirring at a treatment temperature of 70° C. to 150° C. and a treatment time of 5 minutes to 120 minutes. Water can be added during the adsorption treatment. In this case, it is preferred to add 0.5% to 3.0% by mass of water relative to the mass of the polyether polyol. In addition, an antioxidant for preventing deterioration can also be added to the polyether polyol before the adsorption treatment.
[0059] In addition, before adding the adsorbent to the polyether polyol, at least one of inorganic acids such as phosphoric acid, sulfuric acid, sodium hydrogen pyrophosphate, oxalic acid, inorganic acid salts, and organic acids may be added to cause a neutralization reaction. In this case, the adsorbent is added after the neutralization reaction is completed.
[0060] The present invention is not limited to the above-mentioned embodiments and examples described below, and appropriate combinations, substitutions, changes, etc. are possible within the scope of the purpose and spirit of the present invention. Example
[0061] Hereinafter, the present invention will be described in more detail with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples.
[0062] In addition, the measuring methods of various physical properties and the like of Examples and Comparative Examples are as follows.
[0063] <SiO2 / MgO molar ratio and alkali metal content> The SiO 2 / MgO molar ratio and the alkali metal content of the magnesium silicate compound were measured using a scanning fluorescent X-ray analyzer "ZSX Primus IV" manufactured by Rigaku Corporation.
[0064] <BET specific surface area and total pore volume> The BET specific surface area and total pore volume of the magnesium silicate compound were measured using a high-precision evaluation area-pore distribution measuring device "BELsorp-max" manufactured by Microtrack Bell.
[0065] <Liquid pH> The liquid pH of the magnesium silicate compound is measured as follows. 2.0 g of the dried magnesium silicate compound and 40 mL of ion exchange water are placed in a beaker, stirred for 5 minutes with a magnetic stirrer, and then filtered with No. 5C filter paper to measure the pH of the filtrate. The pH of the filtrate is taken as the liquid pH of the magnesium silicate compound.
[0066] <Amount of solid acid> Add 0.1g of dried magnesium silicate compound to a stoppered Erlenmeyer flask, and add 5mL of benzene (Wako Reagent Special Grade). As an indicator with pKa=4.8, add 1mL of 0.1wt% methyl orange solution in benzene to make the dried particles red. Titrate with 0.1mol / L n-butylamine-benzene solution until the dried particles turn yellow, and set the amount of n-butylamine-benzene solution required for the titration as A (mL). After the Erlenmeyer flask is covered with a stopper and left to stand for 24 hours, the dried particles return to red, so titrate with 0.1mol / L n-butylamine-benzene solution again until the dried particles turn yellow, and set the amount of n-butylamine-benzene solution required for the titration as B (mL). Repeat this operation again, and set the amount of n-butylamine-benzene solution required for the titration as C (mL). Based on the following formula, calculate the amount of solid acid according to the total of the titration amounts for 3 times. Solid acid amount (mmol / g) = 0.1 (A + B + C) / 0.1 g
[0067] <Average particle size> The average particle size of the magnesium silicate compound is measured using a particle size distribution measuring device "MICROTRAC MT3000 II Series" manufactured by Nikkiso Co., Ltd. Specifically, first, add 70 mL of a 2.0 g / L sodium hexametaphosphate aqueous solution to 0.7 g of the dried magnesium silicate compound and stir with a magnetic stirrer. Add 2 to 4 mL of the dispersion to a 2.0 g / L sodium hexametaphosphate aqueous solution, circulate the dispersion for 1 minute, and then measure the particle size distribution using the above-mentioned particle size distribution measuring device. The average particle size is calculated from the obtained 50% accumulation (median particle size).
[0068] Next, examples and comparative examples of the present invention will be described.
[0069] Example 1 (Synthesis test) A 1.17 mol / L magnesium sulfate aqueous solution and a No. 3 water glass aqueous solution containing 0.46 mol / L Na2O and 1.44 mol / L SiO2 were continuously injected into a continuous reaction tank in a certain amount to cause a coprecipitation reaction. The reaction temperature was 40°C. The pH of the resulting reaction slurry was 8.9. In addition, the average particle size of the reaction product particles was 8.2 μm. Furthermore, the reaction slurry was suction filtered and dehydrated with a vacuum suction filter, and the solid matter was washed with ion exchange water in an amount of 20 times the weight of the solid matter. The resulting solid matter was slurried to a concentration of 250 g / L and spray dried with a spray dryer.
[0070] The dried product of the magnesium silicate compound of Example 1 thus obtained was subjected to various physical property measurements. As a result, the SiO2 / MgO molar ratio of the magnesium silicate compound of Example 1 was 3.5. The alkali metal content of the magnesium silicate compound of Example 1 was 1.00% by mass. The BET specific surface area of the magnesium silicate compound of Example 1 was 295 m 2 The total pore volume of the magnesium silicate compound of Example 1 is 0.47 cm 3 / g. In addition, the liquid pH of the magnesium silicate compound of Example 1 was 9.8. The solid acid content of the magnesium silicate compound of Example 1 was 0.73 mmol / g. The average particle size of the magnesium silicate compound of Example 1 was 42.2 μm. In addition, the powder X-ray diffraction pattern of the magnesium silicate compound of Example 1 showed that it was amorphous.
[0071] (Adsorption test 1) 160 g of polypropylene glycol (polymerization degree: 3000) dissolved with potassium hydroxide to a potassium concentration of 1400 ppm was placed in a four-necked round-bottom flask, and heated and stirred with a mantle-type resistance heater while replacing with nitrogen. 1.6 mL of ion exchange water was poured in at a time point when the liquid temperature reached 85°C, and then 0.4 g of an adsorbent containing a synthetic magnesium silicate compound was added after the liquid temperature reached 90°C, and heated and stirred for 30 minutes. After 30 minutes, the treated liquid was immediately suction filtered with a suction pressure of 0.02 MPa to obtain a filtrate. The filtrate was titrated with 0.01 N hydrochloric acid to determine the potassium concentration in the filtrate, which was 209 ppm.
[0072] (Adsorption test 2) 160 g of polypropylene glycol (polymerization degree: 3000) dissolved with potassium hydroxide to a potassium concentration of 1400 ppm was placed in a four-necked round-bottom flask, and heated and stirred with a mantle-type resistance heater while replacing with nitrogen. 1.6 mL of ion exchange water was poured in at a time point when the liquid temperature reached 85°C, and then 0.56 g of an adsorbent containing a synthetic magnesium silicate compound was added after the liquid temperature reached 90°C, and heated and stirred for 30 minutes. After 30 minutes, the treated liquid was immediately suction filtered with a suction pressure of 0.02 MPa to obtain a filtrate. The filtrate was titrated with 0.01 N hydrochloric acid to determine the potassium concentration in the filtrate, which was 128 ppm.
[0073] (Adsorption test 3) 160 g of polypropylene glycol (polymerization degree: 3000) dissolved with potassium hydroxide to a potassium concentration of 1400 ppm was placed in a four-necked round-bottom flask, and heated and stirred with a mantle-type resistance heater while replacing with nitrogen. 1.6 mL of ion exchange water was poured in at a time point when the liquid temperature reached 85°C, and then 0.8 g of an adsorbent containing a synthetic magnesium silicate compound was added after the liquid temperature reached 90°C, and heated and stirred for 30 minutes. After 30 minutes, the treated liquid was immediately suction filtered with a suction pressure of 0.02 MPa to obtain a filtrate. The filtrate was titrated with 0.01 N hydrochloric acid to determine the potassium concentration in the filtrate, which was 38 ppm.
[0074] Example 2 (Synthesis test) A 1.17 mol / L magnesium sulfate aqueous solution and a No. 3 water glass aqueous solution containing 0.46 mol / L Na2O and 1.44 mol / L SiO2 were continuously injected into a continuous reaction tank in a certain amount to cause a coprecipitation reaction. The reaction temperature was 40°C. The pH of the resulting reaction slurry was 8.9. In addition, the average particle size of the reaction product particles was 8.2 μm. Furthermore, the reaction slurry was suction filtered and dehydrated with a vacuum suction filter, and the solid was washed with 0.05 mol / L sulfuric acid in an amount of 15 times the weight of the solid, and after ion exchange of sodium in the solid, it was also washed with 20 times the amount of ion exchange water. The resulting solid was slurried to a concentration of 250 g / L and spray dried with a spray dryer.
[0075] The dried product of the magnesium silicate compound of Example 2 thus obtained was subjected to various physical property measurements. As a result, the SiO2 / MgO molar ratio of the magnesium silicate compound of Example 2 was 3.9. The alkali metal content of the magnesium silicate compound of Example 2 was 0.17% by mass. The BET specific surface area of the magnesium silicate compound of Example 2 was 259 m 2 The total pore volume of the magnesium silicate compound of Example 2 is 0.56 cm3 / g. In addition, the liquid pH of the magnesium silicate compound of Example 2 is 9.1. The solid acid content of the magnesium silicate compound of Example 2 is 0.90 mmol / g. The average particle size of the magnesium silicate compound of Example 2 is 43.8 μm. In addition, the powder X-ray diffraction pattern of the magnesium silicate compound of Example 2 is as follows: Figure 1 The shown display is amorphous.
[0076] (Adsorption test 1) The adsorption test was conducted in exactly the same manner as in the adsorption test 1 of Example 1. As a result, the potassium concentration in the filtrate was 211 ppm.
[0077] (Adsorption test 2) The adsorption test was conducted in exactly the same manner as in the adsorption test 2 of Example 1. As a result, the potassium concentration in the filtrate was 104 ppm.
[0078] (Adsorption test 3) The adsorption test was conducted in exactly the same manner as in the adsorption test 3 of Example 1. As a result, the potassium concentration in the filtrate was 34 ppm.
[0079] Example 3 (Synthesis test) A certain amount of 1.17 mol / L magnesium sulfate aqueous solution and a No. 3 water glass aqueous solution containing 0.46 mol / L Na2O and 1.44 mol / L SiO2 were continuously injected into a continuous reaction tank to cause a coprecipitation reaction. The reaction temperature was 40°C. The pH of the resulting reaction slurry was 8.9. In addition, the average particle size of the reaction product particles was 8.2 μm. Furthermore, the reaction slurry was heated and stirred at 90°C for 2 hours. Then, the slurry was suction filtered and dehydrated with a vacuum suction filter, and the solid matter was washed with ion exchange water in an amount 20 times the weight of the solid matter. The resulting solid matter was slurried to a concentration of 250 g / L and spray-dried with a spray dryer.
[0080] The dried product of the magnesium silicate compound of Example 3 thus obtained was subjected to various physical property measurements. As a result, the SiO2 / MgO molar ratio of the magnesium silicate compound of Example 3 was 3.4. The alkali metal content of the magnesium silicate compound of Example 3 was 0.98% by mass. The BET specific surface area of the magnesium silicate compound of Example 3 was 714 m 2 The total pore volume of the magnesium silicate compound of Example 3 is 1.05 cm 3 / g. In addition, the liquid pH of the magnesium silicate compound of Example 3 was 9.6. The solid acid amount of the magnesium silicate compound of Example 3 was 1.65 mmol / g. The average particle size of the magnesium silicate compound of Example 3 was 39.8 μm. In addition, the powder X-ray diffraction pattern of the magnesium silicate compound of Example 3 showed that it was amorphous.
[0081] (Adsorption test 1) The adsorption test was conducted in exactly the same manner as in the adsorption test 1 of Example 1. As a result, the potassium concentration in the filtrate was 123 ppm.
[0082] (Adsorption test 2) The adsorption test was conducted in exactly the same manner as in the adsorption test 2 of Example 1. As a result, the potassium concentration in the filtrate was 70 ppm.
[0083] (Adsorption test 3) The adsorption test was conducted in exactly the same manner as in the adsorption test 3 of Example 1. As a result, the potassium concentration in the filtrate was 40 ppm.
[0084] Example 4 (Synthesis test) A 1.17 mol / L magnesium sulfate aqueous solution and a No. 3 water glass aqueous solution containing 0.46 mol / L Na2O and 1.44 mol / L SiO2 were continuously injected into a continuous reaction tank in a certain amount to cause a coprecipitation reaction. The reaction temperature was 40°C. The pH of the resulting reaction slurry was 8.9. In addition, the average particle size of the reaction product particles was 8.2 μm. Furthermore, the reaction slurry was heated and stirred at 90°C for 2 hours. Then, the slurry was suction filtered and dehydrated with a vacuum suction filter, and the solid was washed with 0.05 mol / L sulfuric acid in an amount of 15 times the weight of the solid, and after ion exchange of sodium in the solid, it was also washed with 20 times the amount of ion exchange water. The resulting solid was slurried to a concentration of 250 g / L and spray dried with a spray dryer.
[0085] The dried product of the magnesium silicate compound of Example 4 thus obtained was subjected to various physical property measurements. As a result, the SiO2 / MgO molar ratio of the magnesium silicate compound of Example 4 was 4.0. The alkali metal content of the magnesium silicate compound of Example 4 was 0.08% by mass. The BET specific surface area of the magnesium silicate compound of Example 4 was 702 m 2 The total pore volume of the magnesium silicate compound of Example 4 is 1.07 cm 3 / g. In addition, the liquid pH of the magnesium silicate compound of Example 4 is 8.4. The solid acid content of the magnesium silicate compound of Example 4 is 1.62 mmol / g. The average particle size of the magnesium silicate compound of Example 4 is 39.8 μm. In addition, the powder X-ray diffraction pattern of the magnesium silicate compound of Example 4 is as follows: Figure 2 The shown display is amorphous.
[0086] (Adsorption test 1) The adsorption test was conducted in exactly the same manner as in the adsorption test 1 of Example 1. As a result, the potassium concentration in the filtrate was 162 ppm.
[0087] (Adsorption test 2) The adsorption test was conducted in exactly the same manner as in the adsorption test 2 of Example 1. As a result, the potassium concentration in the filtrate was 78 ppm.
[0088] (Adsorption test 3) The adsorption test was conducted in exactly the same manner as in the adsorption test 3 of Example 1. As a result, the potassium concentration in the filtrate was 33 ppm.
[0089] Comparative Example 1 (Synthesis test) A 1.35 mol / L magnesium sulfate aqueous solution and a No. 3 water glass aqueous solution containing 0.55 mol / L Na2O and 1.73 mol / L SiO2 were continuously injected into a continuous reaction tank in a certain amount to cause a coprecipitation reaction. The reaction temperature was 40°C. The pH of the resulting reaction slurry was 9.3. In addition, the average particle size of the reaction product particles was 12.8 μm. Furthermore, the reaction slurry was suction filtered and dehydrated with a vacuum suction filter, and the solid matter was washed with ion exchange water in an amount of 20 times the weight of the solid matter. The resulting solid matter was slurried to a concentration of 250 g / L and spray dried with a spray dryer.
[0090] The dried product of the magnesium silicate compound of Comparative Example 1 thus obtained was subjected to various physical property measurements. As a result, the SiO2 / MgO molar ratio of the magnesium silicate compound of Comparative Example 1 was 3.6. The alkali metal content of the magnesium silicate compound of Comparative Example 1 was 1.60% by mass. The BET specific surface area of the magnesium silicate compound of Comparative Example 1 was 126 m 2 / g. The total pore volume of the magnesium silicate compound of Comparative Example 1 is 0.24 cm 3 / g. In addition, the liquid pH of the magnesium silicate compound of Comparative Example 1 is 10.1. The solid acid amount of the magnesium silicate compound of Comparative Example 1 is 0.61 mmol / g. The average particle size of the magnesium silicate compound of Comparative Example 1 is 40.6 μm. In addition, the powder X-ray diffraction pattern of the magnesium silicate compound of Comparative Example 1 shows that it is amorphous.
[0091] (Adsorption test 1) The adsorption test was conducted in exactly the same manner as in the adsorption test 1 of Example 1. As a result, the potassium concentration in the filtrate was 424 ppm.
[0092] (Adsorption test 2) The adsorption test was conducted in exactly the same manner as in the adsorption test 2 of Example 1. As a result, the potassium concentration in the filtrate was 283 ppm.
[0093] (Adsorption test 3) The adsorption test was conducted in exactly the same manner as in the adsorption test 3 of Example 1. As a result, the potassium concentration in the filtrate was 65 ppm.
[0094] The measurement results of various physical properties of each magnesium silicate compound in Examples 1 to 4 and Comparative Example 1 are shown in Table 1. In addition, the potassium concentration in the filtrate in the adsorption test is indicated as "residual K content" in Table 1.
[0095] [Table 1] Table 1
[0096] As shown in Table 1, the adsorbents containing the magnesium silicate compounds of Examples 1 to 4 had a small amount of residual potassium (residual K) in the adsorption test and were able to exhibit very excellent adsorption performance for alkali metals. On the other hand, the adsorbent containing the magnesium silicate compound of Comparative Example 1 had a large amount of residual K in the adsorption test and was insufficient in adsorption performance for alkali metals. Industrial Applicability
[0097] The adsorbent of the present invention has a much higher adsorption capacity than conventional adsorbents containing magnesium silicate compounds, and can adsorb adsorbed substances with a smaller usage amount, so it can be suitably used as an adsorbent for various industrial purposes. The adsorbent of the present invention is particularly useful as an adsorbent for adsorbing and removing an alkali metal-containing basic catalyst in the production of polyether polyols.
Claims
1. An adsorbent comprising an amorphous magnesium silicate compound, characterized in that: The magnesium silicate compound has an alkali metal content of 1.20 mass % or less and a solid acid content of 0.70 mmol / g or more.
2. The adsorbent according to claim 1, wherein The magnesium silicate compound is a compound represented by the following formula (1): (MgO) x ·SiO2·mH2O···(1) In formula (1), x is a number satisfying 0.1≤x≤0.5, and m is a number satisfying 0.1≤m≤1.
5.
3. The adsorbent according to claim 1 or 2, wherein The BET specific surface area of the magnesium silicate compound is 200 m 2 / g~1000m 2 / g.
4. The adsorbent according to any one of claims 1 to 3, wherein The total pore volume of the magnesium silicate compound is 0.40 cm 3 / g~1.50cm 3 / g. 5 . A method for reducing the alkali metal content in a polyether polyol, comprising contacting a polyether polyol containing an alkali metal-containing basic catalyst with the adsorbent according to claim 1 .
Citation Information
Patent Citations
Method for purifying crude polyether and adsorbent
JP2004075674A